Early motor development: risk factors for delay in a population study in Southern Brazil - Zago, Ana Carolina; Trettim, Jéssica Puchalski; Rubin, Bárbara Borges; Scholl, Carolina Coelho; Coelho, Fernanda Teixeira; Ulguim, Fernanda; Pinheiro, Luísa Mendonça de Souza; Matos, Mariana Bonati de; Pinheiro, Ricardo Tavares; Quevedo, Luciana de Avila (Revista de Saúde Pública, 2023)
OBJECTIVE: To assess risk factors associated with motor development delay at three months of age. METHODS: Cross-sectional study with mothers and their three-month-old babies in Southern Brazil. The Bayley-III Scale of Infant and Toddler Development (BSID-III) and the Alberta Infant Motor Scale (AIMS) were used to assess motor development. RESULTS: We evaluated 756 mothers and their three-month-old babies. The overall mean motor development assessed by the BSID-III and the AIMS was 104.7 (SD 13.5) and 55.4 (SD 25.4), respectively. When assessed by the BSID-III, the lowest motor development scores were among babies born by cesarean delivery (p = 0.002), prematurely (p < 0.001), and with low birth weight (p < 0.001). When assessed by the AIMS, babies born prematurely (p = 0.002) and with low birth weight (p=0.004) had the lowest motor development means. After a cluster analysis, we found that babies born by cesarean delivery, with low birth weight, and prematurely had more impaired motor development compared with children born without any risk factors. CONCLUSION: Identifying risk factors allows the implementation of early interventions to prevent motor development delay and, therefore, reduce the probability of other future problems.